The Influence of Pelvic Tilt on Acetabular Orientation and Cover: A Three-Dimensional Computerised Tomography Analysis. Issue 1 (January 2013) - Dandachli, Wael; Islam, Saif Ul; Richards, Robin; Hall-Craggs, Margaret; Witt, Johan
The orientation of the pelvis influences that of the acetabulum. In particular, pelvic tilt in the sagittal plane may lead to inaccurate interpretation of plain pelvic radiographs. We therefore quantified the relationship between this pelvic tilt and acetabular orientation in native hips, and determined whether pelvic tilt affects femoral head cover. We analysed computed tomography scans of 93 hips (36 normal, 31 dysplastic, 26 with acetabular retroversion) and measured acetabular anteversion, inclination, and femoral head cover at pelvic tilt angles ranging from −20° to 20° in relation to the anterior pelvic plane using 5° increments. Pelvic tilt changed acetabular version with a decrease in anteversion ranging from 2.5° to 5° for every 5° of forward tilt. The effect on inclination was less marked and varied. In normal and dysplastic hips pelvic tilt increased apparent femoral head cover. A greater understanding of the influence of pelvic tilt may allow improvements in the radiological diagnosis and surgical treatment of acetabular abnormalities, particularly in relation to acetabular reorientation procedures and femoroacetabular impingement.